How do non-pharmaceutical interventions affect the spread of COVID-19? A literature review - Johannes Pöschl; Rasmus Bisgaard Larsen (Danmarks Nationalbank, 2021)
This memo reviews the academic literature on the effectiveness of non-pharmaceutical interventions in mitigating the spread of COVID-19. Only empirical studies are included. Interventions generally reduce COVID-19 spread but the literature is less conclusive for some interventions than others. Intervention timing and local characteristics are determinants of effectiveness.
Keywords: 330; Coronavirus; Gesundheitspolitik; Gesundheitsvorsorge; Bibliometrie; Dänemark